First record of resting cysts of the benthic dinoflagellate Prorocentrum leve in a natural reservoir in Gujan‐Mestras, Gironde, France. Issue 6 (29th September 2017) - Mertens, Kenneth Neil; Gu, Haifeng; Pospelova, Vera; Chomérat, Nicolas; Nézan, Elisabeth; Gurdebeke, Pieter Roger; Bogus, Kara; Vrielinck, Henk; Rumebe, Myriam; Meteigner, Claire
Abstract : The resting cysts of the benthic dinoflagellate Prorocentrum leve from a natural reservoir in Gujan‐Mestras (Gironde, France) were described in this study. The incubated urn‐shaped cysts gave rise to cells of P. leve . Morphological observations through light microscopy and scanning electron microscopy, particularly of the periflagellar platelets, combined with large subunit ribosomal DNA sequences obtained through single‐cell analysis confirm their affinity to the species P. leve . The cysts were characterized by a specific shape and the presence of an anterior plug. This is the first conclusive evidence for fossilizable resting stages within the Prorocentrales, one of the major orders within the Dinophyceae. Palynological treatments show that the cysts and endospores withstand hydrochloric and hydrofluoric acids. Micro‐Fourier transform infrared analysis on single specimens suggests that the composition of the endospore is cellulosic and the cyst wall a more robust, noncellulosic β‐glucan. The spectra overall are similar to other published spectra of resting cysts from autotrophic, planktonic dinoflagellates.